Leadership Styles and its impact on Organization Performance: A study on Women Entrepreneurs Leadership Style in India - Ashutosh Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fast changing economical, sociological, and technological environment in past 20 years resulted in the invasion of women into Indian workforce.Other than huge representation in the workforce, it resulted in the economic displacement of investment with an emphasis on short-term returns.It has become a catalyst for organizational change for growth in recent decades and also focused on organizational overhaul. Organizational transformation, faith in their management, collaboration, diversity and the roots of a modern model of leadership are largely part of this organizational shift. A leader is one that handles the team successfully for the company. In order to become a success entrepreneur, women must cultivate leadership qualities. The present study seeks to examine the linkage between the leadership styles of women entrepreneurs (ELS) and organizational performance (OP). In this research, dependent and independent variables are involved. On the other hand, the dependent factor is the leadership style of women entrepreneurs. The independent factor is organizational success. Based on these factors, a questionnaire was designed. A total of 43 women entrepreneurs out of 84 were included in the research who responded. Questionnaires were distributed in Delhi and Pune to women entrepreneurs. This research focuses on women entrepreneurs' leadership positions and their effect on organizational efficiency. In the future, the analysis should also take into consideration other variables. This analysis is used to study the relation between ELS and OP.